1, 8-Naphthyridine-based fluorescent receptors for picric acid detection in aqueous media. Issue 24 (20th November 2015) - Chahal, Mandeep K.; Sankar, Muniappan
Abstract : Naphthyridinic fluorescent receptors (1 and2 ) were utilized for the selective detection of picric acid (PA) in aqueous media and are able to detect ∼1 ppm of PA via a fluorescent 'turn off' mode. Abstract : We utilized the potential applications of 1, 8-naphthyridine-based sensors for the detection of various nitroaromatics such as picric acid (PA), 3-nitrophenol (NP), 2, 4-dinitrotoluene (DNT), 1, 3-dinitrobenzene (DNB), 4-nitrotoluene (NT), nitrobenzene (NB) and nitromethane (NM). Among the various nitroaromatic analogues, nap-OH (1 ) and nap-Cl (2 ) sense picric acid (PA) much more efficiently and with very low detection limits (1.12 and 0.96 ppm, respectively), owing to favourable electron and/or energy transfer mechanisms along with potential electrostatic interactions. Interestingly, both sensors1 and2 detect PA in aqueous media (H2 O/CH3 OH, 8 : 2) with the same quenching efficiency as in neat CH3 OH, resulting in cheap, sensitive and environmentally friendly detection methodology. Therefore, use of these molecules for picric acid detection in aqueous and methanolic solutions, having low detection limits along with exceptional quenching constants ( k SV ) meets the present need. In addition, sensors1 and2 exhibit instant visualization of trace amounts of PA in both the solid-state and when using test strips.